Seni Tari Kontemporer Sebagai Media Komunikasi Antar Generasi di Kampung Dadap Kota Tangerang Selatan. - Nuriman, Dian Agustine; Octory, Gadis (Universitas Mercu Buana, 2024)
Dance is a type of non-verbal communication that conveys messages through coordinated movements to the audience. Currently, contemporary dance is popular with Generation Z and also the Millennial generation who are at the age of having teenage children. This happens because digital communication media is so massive in presenting new cultural offerings through dance, especially on social media, that contemporary dance is popular with Generation Z and Millennials. The rise of problems in teenagers is often caused by a lack of good communication through interpersonal communication between parents and children. Along with the growth in social media consumption that occurs in Indonesia, it also affects the lack of communication within the family. Therefore, by conducting contemporary dance training carried out by mothers and children in Dadap village, South Tangerang, it is hoped that it can become a medium of communication between generations to create harmonious and useful collaboration activities in fostering communication between generations of parents and children in Dadap village. South Tangerang.